2020
DOI: 10.1016/j.fsigen.2020.102269
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating touch deposits through cellular characterization of hand rinses and body fluids with nucleic acid fluorescence

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Inferring the body fluid(s) present in stains is, in the context of secondary (or more) transfer, important for two reasons: (1) to assess the cellular content of the primary stain in relation to the DNA recovered from the evidentiary sample as some fluids have very high cellular content (for example nasal secretion), whilst others contain much fewer cells (for instance urine) and (2) to assess whether the body fluid involved is likely to occur in what is suggested) to be the primary location [41]. For example, intimate body fluids (vaginal cellular material, menstrual secretion, semen) can be found in underpants of the wearer, but are less expected on hands or touched items [42][43][44]. Saliva and nasal secretion, on the other hand, can reside on hands or items, and blood could occur when people have (small) wounds.…”
Section: Addressing Alternative Scenariosmentioning
confidence: 99%
“…Inferring the body fluid(s) present in stains is, in the context of secondary (or more) transfer, important for two reasons: (1) to assess the cellular content of the primary stain in relation to the DNA recovered from the evidentiary sample as some fluids have very high cellular content (for example nasal secretion), whilst others contain much fewer cells (for instance urine) and (2) to assess whether the body fluid involved is likely to occur in what is suggested) to be the primary location [41]. For example, intimate body fluids (vaginal cellular material, menstrual secretion, semen) can be found in underpants of the wearer, but are less expected on hands or touched items [42][43][44]. Saliva and nasal secretion, on the other hand, can reside on hands or items, and blood could occur when people have (small) wounds.…”
Section: Addressing Alternative Scenariosmentioning
confidence: 99%
“…Several other papers demonstrated or alluded to observing differences in the quantities of DNA deposited, which was attributed to differences in shedder status, for example [51,78,150,152]. However, Miller et al [95] found that individuals who deposited extremely large amounts of DNA by touch one day may deposit no detectable DNA on another day despite a restriction on handwashing close in time to deposition, leading the authors to question the concept that there are consistently good shedders, at least through the palms of hands.…”
Section: Shedder Statusmentioning
confidence: 99%
“…To explore source differences and gain insight into associations with DNA content, Burrill et al [51] used flow cytometry and microscopic examination to generate granularity, size and nucleic acid fluorescence data of washed and unwashed hands, as well as saliva, nasal and eye wash that could be sources of transferred DNA onto hands. They found that hand rinses consisted mainly of anucleate corneocytes, many of which also stained positive for nucleic acids, and suggested the need for further research on the recovery and analysis of corneocyte DNA, which they report was previously assumed to be negligible.…”
mentioning
confidence: 99%
“…The shed corneocytes from handled objects may be sufficiently distinct to permit separation from other cell types or even by donor, using morphology and autofluorescence [27,28]. When hand rinses were separated using flow cytometry, corneocyte cells indicated much higher levels of nucleic acid fluorescence than the subcellular fragment population [29]. Some studies report negligible DNA from these shed cells, while some yield useable DNA levels or full profiles, leaving ambiguity and variability [14,30,31].…”
Section: Introductionmentioning
confidence: 99%